Effects Of Some Fungal Secondary Metabolite Against Some Cancer Cell Line (Bangladesh Journal of Medical Science, 2023)
The promising feature of the fungi from the marine environment as a source for anticancer agents belongs to the fungal ability to produce several compounds and enzymes which contribute effectively against the cancer cells growth. Moreover, the compounds produced during the secondary metabolic process acts by changing the cell morphology and DNA fragmentation leading to apoptosis of the cancer cells. When compared to the other chemicals in the investigation, gliotoxin demonstrated the most cytotoxic effect. These findings suggest that gliotoxin could be a potential virulence factor of Aspergillus fumigatus during infection. Anti Cancer, the dreadful disease that spreads throughout the body, bringing its cells closer to death than life expectancy, will be defeated or at least slowed by natural plants. Many researchers and clinicians are familiar with the treatment of numerous plants, such as Rheum ribes. Cancer studies have shown that the usage of some medicinal herbs can help to minimize the severity of this dreadful disease, and plant care is also well understood.Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.133-137